WANDERLUST ON THE SILVER SCREEN: THE INFLUENCE OF DIL CHAHTA HAI ON TOURIST BEHAVIOUR - Choudhary, Rama; Mathur, Shipra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines how films affect tourist choices, specifically focusing on the Hindi film Dil Chahta Hai (2001). The film features relatable characters, stunning visuals, and themes of adventure and love, motivating viewers to visit places like Goa and Sydney. A qualitative method is used to analyze the film's story, visual style, and themes, along with social media posts, reviews, and travel blogs to evaluate its effect on tourism. The results show that films play a key role in sparking a desire to travel by showcasing beautiful locations and engaging stories that connect with viewers emotionally. By highlighting Goa's beaches and Sydney's iconic sites as backdrops for friendship and self-discovery, Dil Chahta Hai has made these places popular travel spots. The film's cinematic techniques such as non-linear storytelling, rich visuals, and moving music enhance its cultural and tourist appeal. The study finds that cinema not only entertains but also has a strong impact on actual travel habits, inspiring audiences to turn their film-inspired aspirations into real-life adventures.